Static Pullout Strength of Power Actuated Fasteners in Steel: State-of-the-Art Review - Beck, Hermann; Engelhardt, Michael; Glaser, Neil (Engineering Journal, 2003)
Power-actuated fasteners (PAFs) are high strength nails used for making attachments to steel or concrete. PAFs driven into steel are the subject of this paper. PAFs are driven into steel using either powder-actuated or pneumatically driven tools and provide an alternative to more conventional fasteners such as welds, bolts, and screws. Power-actuated fastening systems for steel have been available for over 50 years. However, relatively little research information has been published on this fastening system in journals or in other engineering research and design literature. The purpose of this paper is to provide an overview of power-actuated fastening for steel and to provide a state of the art review on the static pullout strength of individual power-actuated fasteners in steel. Much of the past research and testing information on PAFs is contained in unpublished or proprietary research or test reports that are not widely or easily available to researchers and engineers. This lack of public domain literature on PAFs for steel is the primary motivation for this paper, which summarizes test data that is not otherwise easily available.